2019
DOI: 10.1101/602177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Curvature increases permeability of the plasma membrane for ions, water and the anti-cancer drugs cisplatin and gemcitabine

Abstract: In this work the permeability of a model asymmetric plasma membrane, for ions, water and the anti-cancer drugs cisplatin and gemcitabine is studied by means of all-atom molecular dynamics simulations. It is shown that permeability of the membranes increases from one to three orders of magnitude upon membrane bending depending on the compound and the sign of curvature. Our results show that the membrane curvature is an important factor which should be considered during evaluation of drug translocation.TOC GRAPH… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Numerous studies show that there are many substances, interfacially active peptides [55][56][57] and non-peptide compounds that can influence membrane curvature, and vice versa. Yesylevskyy and colleagues have shown that the permeability of the model lipid membrane for cisplatin and gemcitabine depends on the curvature [58]. Barry and colleagues showed that curcumin, a lipophilic drug, binds to dimyristoyl-phosphocholine (DMPC) with a transbilayer orientation, anchoring to the bilayer by a hydrogen bond to the phosphate group, while, in dipalmitoleoyl-glycero-phosphoethanolamine (DiPOPE) vesicles, it promotes and stabilizes the formation of the inverted hexagonal (HII) phase.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies show that there are many substances, interfacially active peptides [55][56][57] and non-peptide compounds that can influence membrane curvature, and vice versa. Yesylevskyy and colleagues have shown that the permeability of the model lipid membrane for cisplatin and gemcitabine depends on the curvature [58]. Barry and colleagues showed that curcumin, a lipophilic drug, binds to dimyristoyl-phosphocholine (DMPC) with a transbilayer orientation, anchoring to the bilayer by a hydrogen bond to the phosphate group, while, in dipalmitoleoyl-glycero-phosphoethanolamine (DiPOPE) vesicles, it promotes and stabilizes the formation of the inverted hexagonal (HII) phase.…”
Section: Discussionmentioning
confidence: 99%
“…Food and Drug Administration. 3,4 Since then, an impressive amount of experimental 3,[5][6][7][8][9][10][11] and theoretical [12][13][14][15][16][17] work has been carried out to elucidate the mechanism of action of cisplatin, which is widely employed as chemotherapeutic drug in the treatment of patients with bladder, ovarian, head and neck, lung, testicular, cervical, esophageal, breast and brain cancers. 18 Moreover, the success shown by cisplatin motivates the design and investigation of many other platinum-based compounds with improved biophysiological properties in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study showed that positive (convex) and negative (concave) curvature increases water permeability on an asymmetric composition mimicking the plasma membrane. 65 Positive curvature implies that the polar heads get further apart which creates packing defects 66 facilitating water entry into the membrane. For negative curvature, it is less clear why water permeability is enhanced compared to a flat membrane.…”
Section: Simulations Of Dopc Membranes Under a Directional Pressurementioning
confidence: 99%